Hubungan Kesegaran Jasmani dan Motivasi Belajar dengan Hasil Belajar Siswa Kelas XI SMA Negeri 5 Bukittinggi - Muhammad Ashar (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2014)
The background of this study is the lack of student learning outcomes, some students are less to enjoy some sports activities, not eager to practice sports activities, are less confident in doing sports activities, physical health of students who are less supportive. The objectives of this research are 1) the relationship of physical fitness to the learning outcomes of students in class XI SMA 5 Bukittinggi, 2) the relationship of learning motivation on learning outcomes of students of class XI of SMAN 5 Bukittinggi, 3) relationship of physical fitness and motivation toward learning outcomes of students in class XI SMA 5 Bukittinggi. The research is a descriptive correlational. The population in this study amounted to 149 students, the sample used is proportional random sampling technique of obtained 25 Students. The data analysis is used in this research is product moment correlation formula. The results of this study indicated that physical fitness closely related to students’ learning outcomes of SMA 5 Bukittinggi r>0.654> 0.396, students' motivation relates to students’ learning outcomes r> rtabel 0.453> 0.396. Physical fitness related to student learning outcomes of SMA 5 Bukittinggi r> rtabel 0.488> 0.413, learning motivation relates to student learning outcomes women r> rtabel 0.420> 0.413. Physical fitness and motivation of students learning together in student learning outcomes associated with men's 51.5%. Physical fitness and the motivation to learn together related to students’ learning outcomes of 76.9%.